Fungsi agama dalam kehidupan individu - Zahro, Salsabila Raudhatuz (Maliki Interdisciplinary Journal, 2024)
Religion has a very important role in the life of individuals, and influencing various aspects both physical and psychological. In this article we examine some of the functions of religion in an individual's life, including providing moral guidance, emotional support, a sense of identity, and answers to existential questions. Despite ongoing social and cultural shifts today, the role of religion will remain influential in society.